The blood of Olympus - Riordan, Rick (Puffin Melbourne, Victoria, 2020)
In The Blood of Olympus, the fifth installment of the Heroes of Olympus series, demigods from both Greek and Roman backgrounds unite to prevent the rise of the Earth goddess Gaea. As they face formidable foes and inner struggles, the group must work together to fulfill their destinies while embarking on a perilous quest to save the world.